2002
DOI: 10.1007/s00432-002-0377-7
|View full text |Cite
|
Sign up to set email alerts
|

Realtime visualization of tumor cell/endothelial cell interactions during transmigration across the endothelial barrier

Abstract: Realtime laser scanning confocal microscopy leads to a better understanding of the complex and dynamic cell-to-cell and cell-to-matrix interactions during the extravasation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 16 publications
1
26
1
Order By: Relevance
“…These observations are consistent with study by Burns et al 7 for the neutrophil migration across HUVEC monolayers, suggesting a similar mechanism by which TCs and leukocytes accomplish their transmigration across microvessel walls. These results are also consistent with our previous study on TC adhesion to bEnd3 monolayers 19 , suggesting that adhesion is the initial step for TC extravasation 30, 37, 60 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These observations are consistent with study by Burns et al 7 for the neutrophil migration across HUVEC monolayers, suggesting a similar mechanism by which TCs and leukocytes accomplish their transmigration across microvessel walls. These results are also consistent with our previous study on TC adhesion to bEnd3 monolayers 19 , suggesting that adhesion is the initial step for TC extravasation 30, 37, 60 .…”
Section: Discussionsupporting
confidence: 93%
“…Many previous studies investigated TC adhesion to microvessel walls as the initial step for extravasation 30, 37, 60 . Using an in vitro real-time model, Heyder et al 31 demonstrated that invasive human bladder carcinoma cell line T24 irreversibly damages the ECs by inducing apoptosis at the site of TC infiltration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also difficult to predict how changes in stiffness between the PDMS and gel affect extravasation mechanisms. Furthermore, most studies of extravasation or TEM across planar EC monolayers 12, 13, 15, 16 are limited in their physiological relevance.…”
Section: Introductionmentioning
confidence: 99%
“…administration. The extravasation of tumor cell clusters derived from the invasive human bladder carcinoma cell line T24 occurs in a relatively short time-frame up to 4 h after adhesion to the endothelium [24], suggesting that melanoma cells inoculated i.v. are also trapped and adhered to endothelium in the lung and then extravasate from the vein within a few hours.…”
Section: Discussionmentioning
confidence: 99%